THE ROLE OF INCLUSIVE LEADERSHIP IN REFINING THE SPIRITUAL EXPERIENCE - Dr. Hameedah Ghjaer Chraimukh; Dr.Laith Ali Muttar; Dr.Riyadh Malik Al-Falahi (Scholars Digest Publishing, 2023)
This study aimed to measure the role of inclusive leadership in refining the spiritual experience in organizations. The study highlighted the need for organizations to adopt a new and appropriate model in refining the spiritual experience, as it worked to test the relationships of correlation and influence between comprehensive leadership with its elements (communication, support and guidance, and accessibility) and the spiritual experience represented in (spiritual support, spiritual openness).The targeted organizations were the colleges of Al-Qadisiyah University, and the study adopted the descriptive analytical approach for the opinions of a sample of its leaders, who numbered (67) leaders, which reached (95%) of the study population. The questionnaire was used as a tool for collecting data on its variables The study conveyed an encouraging message to the researched colleges in particular and organizations in general, which is that the refinement of spiritual experience can be achieved when those colleges are able to ensure the required level of comprehensive leadership, and that comprehensive leadership can, through its behaviors, play a pivotal role in refining spiritual experience.The study came out with a number of recommendations, the most important of which is that the leaders in the surveyed colleges should be keen to encourage their affiliates, represented by faculty members, to refine their educational experiences through support and spiritual openness with co-workers and the external environment in order to produce a high-level scientific outcome. The study also presented some suggestions for future studies that could contribute to enriching the administrative literature.
Keywords: comprehensive leadership, spiritual experience, Al-Qadisiyah University.